Phytochemical screening, tlc profiling and antifungal activity of elaies guineensis against fusarium oxysporum / Mohd Rasyid Ahmad - Ahmad, Mohd Rasyid (Faculty of Plantation and Agrotechnology, 2019)
Fusarium wilt is one of the diseases that often-attacked plants in Malaysia such as bananas, tomatoes, black pepper, rice and others. The various methods have been made to control Fusarium wilt diseases including the use of chemicals. However, the extensive use of chemicals will become a negatively impacts to environment and plants are more susceptible to pests and diseases. Hence, this study was used wasted product with plant extract method from part of Elaeis guineensis such as empty fruit bunches (EFB), pressed palm fibres (PPF), kernel, leaf and trunk by using methanol solvent to control Fusarium oxysporum. TLC profiling was used to identify the best solvent to separate the pure compound. While the phytochemical screening was analyzed for the presences of alkaloid, flavonoid, terpenoid, tannins and saponins. All the extract was evaluated their antimicrobial properties with 25 and 50 ppm based on disk diffusion method. Trichoderma sp. as a positive standard control against Fusarium oxysporum. The results of phytochemical screening process confirmed the presence of alkaloids, flavonoids, tannins and terpenoid in Elaies guineensis extract. Hexane: Ethyl acetate, 2:8 is the best solvent system which it possed in several compound especially in kernel, leaf and PPF with 6,3 and 2 compounds. Antifungal activity revealed that trunk extract to control Fusarium oxysporum with moderate inhibitory zone 10.67mm in 25mg/mL and 14.33mm in 50mg/mL followed by leaf with slightly inhibitory zone 9.67mm in 25mg/mL and 13.00mm moderate inhibitory zone in 50mg/mL. These finding provided the evidence that wasted product from part of Elaies guineensis had a potential for replacement of Trichoderma sp. against Fusarium oxysporum.